Block Boundary Analyses to Identify Martensite and Bainite. (2015) - Morito, S.; Pham, A.H.; Hayashi, T.; Ohba, T.
Abstract: Identification of martensite and bainite in the ferrous alloys is difficult because both morphologies contain similar complex microstructures. Recently, it was pointed out that the frequencies of block boundaries in the morphologies are different from each other. In the present study, a simple method for identifying martensite and bainite using the profile of block boundaries is suggested. This method was applied for upper and lower bainites and lath martensite in Fe–0.6mass%C alloy. The lower bainite can be separated by the ratio of 52 degrees / <011>α' boundaries. Furthermore lath martensite and upper bainite are identified using near twin block boundaries and block boundary density.